A comprehensive review on MIMO antennas for 5G smartphones: Mutual coupling techniques, comparative studies, SAR analysis, and future directions - Al Gburi, Ahmed Jamal Abdullah; Jemaludin, Nazrin Haziq; Hamdy Elabd, Rania; Saeidi, Tale; Akbar, Muhammad Firdaus; Mohd Ibrahim, Imran; Zakaria, Zahriladha (Elsevier B.V., 2024)
Multiple-input multiple-output (MIMO) technology has become a key enabler for 5G smartphones, significantly enhancing data throughput and connectivity. By incorporating multiple antennas into the compact design of modern smartphones, MIMO technology improves spectral efficiency and network capacity. This comprehensive review examines the fundamental characteristics of MIMO antennas designed for 5G smartphones. The study explores various mutual coupling techniques used to mitigate interference between closely spaced antennas, thereby enhancing system performance. A comparative analysis of different MIMO antenna configurations is presented, highlighting their respective advantages and limitations in 5G applications. Additionally, the review includes specific absorption rate (SAR) analysis to ensure user safety by adhering to regulatory standards and addressing health concerns associated with prolonged exposure to electromagnetic fields. Finally, the paper outlines future directions for MIMO antenna research, emphasizing the need for innovative design strategies to accommodate the evolving landscape of wireless communication.